Revision of the genera Cyphonethes Verhoeff, 1926 and Titanethes Schioedte, 1849 (Isopoda: Oniscoidea: Trichoniscidae) with a description of a new genus and three new taxa - Karaman, Ivo M.; Horvatović, Mladen (Zootaxa, 2018)
A taxonomic study of two troglobite genera resulted in remarkable changes to their composition and our perception of their relationship. The genus Titanethes is treated as monotypic, with one newly described taxon, Titanethes albus matovici n. ssp. One species is transferred from Titanethes to the genus Cyphonethes, Cyphonethes biseriatus (Verhoeff, 1900) comb. nov. A species and a genus are synonymized, Microtitanethes licodrensis syn. nov. The diagnosis of the genus Cyphonethes is amended and revised using comparative morphology of adult males. A new species, Cyphonethes tajanus n. sp, is described. A close relationship between the genera Titanethes and Spelaeonethes is established. Cetinjella monasetrii n. g., n. sp, is described as a new genus and species close to the genus Cyphonethes. It is assumed to be a higropetric cave inhabitant, based on its pereopode structure, with elongated fused dactylus and unguis, and partly by its slightly modified mouthparts. Unique water uptake (for the water conducting system) by the dorsal surface of the frontal pereionite is also assumed for the species, based on the presence, distribution and orientation of specific small scales. The presence and structure of male tergal glands in the genus Tithanethes are treated as taxonomically irrelevant.